-5(7-10x)=

Simple and best practice solution for -5(7-10x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(7-10x)= equation:


Simplifying
-5(7 + -10x) = 0
(7 * -5 + -10x * -5) = 0
(-35 + 50x) = 0

Solving
-35 + 50x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '35' to each side of the equation.
-35 + 35 + 50x = 0 + 35

Combine like terms: -35 + 35 = 0
0 + 50x = 0 + 35
50x = 0 + 35

Combine like terms: 0 + 35 = 35
50x = 35

Divide each side by '50'.
x = 0.7

Simplifying
x = 0.7

See similar equations:

| 8-3.8k=-4 | | -16t+128t+320=0 | | 5x+5y+5z=300 | | 5y-13=7y-19 | | -32-3.5f=-17 | | -2x+3y=40 | | 1.2y-1.8=7.8 | | 10+3x=2x+9 | | b.3-6=-2 | | .75z-1=.25(z+8) | | 3x^2=7-20x | | 12y-11=y^2 | | 2(x-3)-3(5x-2)=1 | | 16x^2=56x-49 | | 2x+-15x+6-6=10 | | t^2+44+15t=0 | | 3x-4=-x+44 | | 3(x-2)-3=5x-1 | | 6x-9y=-27 | | 7n-28=3(3n-7) | | (5b-4)(6b-6)= | | 5b-4*6b-6= | | 7-7x=92-42x | | 9.-4+3=15 | | -7x+5+10=3x-7-2x | | u.5+6=2 | | 5(y+2)=20 | | 5b-20=18+3b | | 7x=56(9) | | 20-5b=18+3b | | 0=x^4-21(logx) | | 6x=0+35 |

Equations solver categories